2019
DOI: 10.7888/juoeh.41.303
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nutrition Therapy and Rehabilitation on Acute and Critical Illness: A Systematic Review

Abstract: There have been no reviews describing the efficacy of the combination of both rehabilitation and nutritional treatments. This systematic review aimed to assess the effects of nutritional therapy on patients with an acute and critical illness undergoing rehabilitation. Online searches using PubMed (MEDLINE), Cochrane Central Register of Controlled Trials, EMBASE (ELSEVIER), and Ichu-shi Web databases identified 986 articles, and 16 additional articles were found through other sources. Each trial assessed for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…LBM did not change markedly in the intervention group. Two RCTs [7,8] were premised on restarting oral intake after admission [17]. In our patient, LBM improved from 29.7 kg to 38.3 kg.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…LBM did not change markedly in the intervention group. Two RCTs [7,8] were premised on restarting oral intake after admission [17]. In our patient, LBM improved from 29.7 kg to 38.3 kg.…”
Section: Discussionmentioning
confidence: 68%
“…Jones et al [7] did not report the total energy, total protein intake, findings, or muscle strength. Regarding the outcome data, a systematic review judged a high risk of bias due to a lack of power and follow-up for over 20% of the participants [17]. In the study by Hagerova et al [8], participants were excluded if they had weight loss recently.…”
Section: Discussionmentioning
confidence: 99%
“… 65 As suggested in a study, patients might be burdened by the nutritional treatment both during hospitalization and after discharge. 66 Considering that qualitative research could contribute to practical intervention delivery insights, this review highlights the need for more qualitative studies investigating the perspectives of the patients and/or their caregivers, in an effort to treat the person as a whole. Current qualitative studies have investigated the association between nutrition and the PF of ICU patients in either a nation (ie, Japan) 47 or certain types of ICU patients (ie, chronic critical illness patients).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from nutritional interventions solely, it is recommended that bundled or synergistic therapies should be taken into consideration, 51 such as combined nutritional and physical interventions, as this enhanced synergistic treatment may increase muscle mass, and improve activities of daily living within a short period after discharge for ICU patients. 66 …”
Section: Discussionmentioning
confidence: 99%
“…A recent review of nutrition and ICU rehabilitation included 2 studies which trialled oral nutritional supplementation (initiated post-ICU) combined with enhanced physical rehabilitation, and found conflicting results 6 . Future studies are indicated to determine the optimum nutrition required in both the ICU and post-ICU period, and how this can best support physical interventions.…”
Section: Treating Icuaw: Post-icu Interventionsmentioning
confidence: 99%